2016
DOI: 10.1371/journal.pone.0155277
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activity Onset Prior to Landing in Patients after Anterior Cruciate Ligament Injury: A Systematic Review and Meta-Analysis

Abstract: Muscle activation during landing is paramount to stabilise lower limb joints and avoid abnormal movement patterns. Delayed muscle activity onset measured by electromyography (EMG) has been suggested to be associated with anterior cruciate ligament (ACL) injury. Therefore, the aim of this systematic review and meta-analysis was to test the hypothesis if ACL-injured patients display different results for muscle onset timing during standard deceleration tasks compared to healthy control participants. PubMed, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…This remains unclear based on the retrospective design of our study. While a recent systematic review and meta-analysis ( Theisen et al, 2016 ) suggests that muscle activity onset is not associated with increased ACL injury risk, current evidence is still scarce and weak ( Theisen et al, 2016 ). Future prospective studies should examine whether neuromuscular deficits and altered muscle onsets are present before ACL injuries.…”
Section: Discusionmentioning
confidence: 99%
“…This remains unclear based on the retrospective design of our study. While a recent systematic review and meta-analysis ( Theisen et al, 2016 ) suggests that muscle activity onset is not associated with increased ACL injury risk, current evidence is still scarce and weak ( Theisen et al, 2016 ). Future prospective studies should examine whether neuromuscular deficits and altered muscle onsets are present before ACL injuries.…”
Section: Discusionmentioning
confidence: 99%
“…The ACL tears occur soon after the initial ground contact 5,6 and too quickly for reflexive muscular activation (>100 milliseconds) to prevent injuries 7 . Zebis et al (2009) 8 showed that abnormal co-activation of thigh muscles performing side-cutting tasks predisposes for future ACL injury, therefore modulating muscle activity prior to landing seems to be crucial to avoid excessive joint rotations and to protect ACL from dangerous loading 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the electromyographic (EMG) activity prior to landing in ACL reconstructed (ACL-R) subjects, results are controversial in reporting successful or abnormal neuromuscular strategies performing jump-landing tasks 16,17 . A recent review of Theisen et al(2016) 10 describes in details pre-landing muscle activity in ACL injured and reconstructed subjects reviewing the literature from 1980 to 2015. The review underlined the weakness of current evidences on this topic recognizing clinical and methodological heterogeneity, such as the type of graft, time from surgery and level of physical activity as main weak points of existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while the KOOS was developed for an osteoarthritic population, 2 and the IKDC for a range of knee injuries, 4 they have both been validated in ACL populations 4,34 and are both commonly used in ACLrelated studies. 35 As such, it was important to include them in the current analyses. Furthermore, the KNEES is currently only valid in Danish and therefore its international scope is as yet limited.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting our results, the first limitation to consider is that, unlike the KNEES, not all our PROMs are specifically designed for measuring subjective function in ACLd and ACLr patients. Nevertheless, while the KOOS was developed for an osteoarthritic population, and the IKDC for a range of knee injuries, they have both been validated in ACL populations and are both commonly used in ACL‐related studies . As such, it was important to include them in the current analyses.…”
Section: Discussionmentioning
confidence: 99%